Exploring entrepreneurial culture and its socio-cultural determinants: In case of Woldia University graduating students - Abriham Ebabu Engidaw (Journal of Innovation and Entrepreneurship, 2021)
The purpose of this study was to explore entrepreneurial intention and its determinants: in the case of Woldia University graduating students. To achieve its objectives, the study employed a descriptive and explanatory research design, and in the study, a cross-sectional study was conducted through a mixed research approach. The target population of the study was 223 regular first-degree 2018 graduating students of Woldia University, Management Department, and their instructors in the study area. The sample size was 143 respondents. The study result showed that majority of the respondents did not plan to start their own knowledge-based business. This was essentially due to the lack of competence in transforming ideas in to practice and commercializing it to create their own business. Correspondingly, prodigious attention should be given to have an entrepreneurial orientation in the contents and methods of teaching at all levels of education systems primary, secondary, and higher educational institutions and use different awareness-raising mechanisms in the country.
Keywords: 650; Determinants of entrepreneurship; Employment; Entrepreneurial culture